The Activity of CCL18 is Principally Mediated through Interaction with Glycosaminoglycans - Krohn, Sonja (Frontiers Media S.A., 2013)
The CC chemokine ligand 18 (CCL18) was first identified as a chemoattractant for naïve T cells. It has been reported to recruit T and B lymphocytes, and we show here, natural killer (NK) cells, but with low efficacy. Investigation of its ability to elicit G-protein-coupled signaling showed that it does not involve extracellular signal-regulated kinase (ERK) phosphorylation, and it is not able to induce receptor internalization, as assessed on CCR3. CCL18 has recently been reported to possess activities unrelated to cellular recruitment, but it had no effect on T lymphocyte proliferation. We postulated that a more potent chemoattractant may be produced under inflammatory conditions but only minor truncations were observed, with the major form being the full-length protein. In view of the lack of potent immunomodulatory properties, we wondered if binding to CCL18 by the tick chemokine binding proteins Evasin-1 and -4 was an artifact of the methods used, but complex formation was confirmed by size exclusion chromatography, and abrogation of its binding to, and antagonism of, CCR3. Its receptor has remained elusive since its cloning in 1997, although it has been reported to induce migration of breast cancer cells by signaling through PITPNM3, but we show that this receptor is not expressed on lymphocytes. We have developed a radiolabeled equilibrium competition binding assay and demonstrated that it bound with high affinity to peripheral blood leukocytes (PBLs), but the binding was displaced similarly by both unlabelled CCL18 as well as heparin. Both heparin binding and binding to PBLs are considerably abrogated by mutation of the BBXB motif in the 40s loop suggesting an essential role of the CCL18-glycosaminoglycan interaction.